MicroRNA-126 regulates macrophage polarization to prevent the resorption of alveolar bone in diabetic periodontitis. (June 2023) - Li, Jiajun; Liu, Yue; Lai, Wen; Song, Liting; Deng, Jiayin; Li, Changyi; Jiang, Shaoyun
Abstract: Objective: This study aims to investigate the effects of microRNA-126 (miR-126) on the macrophage polarization in vitro and alveolar bone resorption in vivo. Design: The relationship between miR-126 and MEK/ERK kinase 2 (MEKK2) was confirmed by dual-luciferase reporter assay. Real-time quantitative polymerase chain reaction, enzyme-linked immunosorbent assay or Western blot was used to detect the changes of miR-126, inducible nitric oxide synthase (iNOS), arginase-1 (Arg-1), tumor necrosis factor (TNF)-α, interleukin (IL)-10, MEKK2 and MEKK2-related pathways: mitogen-activated protein kinase (MAPK) and nuclear factor kappa-B (NF-κB) in RAW264.7 macrophages challenged with Porphyromonas gingivalis ( P. gingivalis ) lipopolysaccharide (LPS) and/or high glucose and/or miR-126 mimic. In mice with diabetic periodontitis, the expressions of iNOS and Arg-1 in gingiva, and alveolar bone level were detected after miR-126 mimic injection. Results: MiR-126 could directly bind with MEKK2 3′-untranslated region (UTR). MEKK2, phosphorylation of NF-κB and MAPK signaling proteins, TNF-α and iNOS increased ( P  < 0.05), while miR-126, Arg-1 and IL-10 were inhibited ( P  < 0.05) in macrophage challenged with high glucose and/or P. gingivalis LPS, however, miR-126 mimic reversed these effects ( P  < 0.05). The expressions of iNOS in gingiva and alveolar bone resorption were elevated ( P  < 0.05), the expression of Arg-1 in gingiva decreased ( P  < 0.05) in mice with diabetic periodontitis, which could be inhibited by miR-126 mimic. Conclusions: miR-126 might prevent alveolar bone resorption in diabetic periodontitis and inhibit macrophage M1 polarization via regulating MEKK2 signaling pathway. Highlights: High glucose and lipopolysaccharide induce macrophage M1 polarization. MicoRNA-126 inhibits macrophage M1 polarization via targeting MEK/ERK kinase 2. MicoRNA-126 prevents alveolar bone resorption in diabetic periodontitis.